(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the political, cultural and educational work carried out in Uzbekistan in 1919-1930s to liberate women, involve them in social life and the education system. The organization of women’s departments in the Turkestan region, the opening of girls’ schools and boarding schools, efforts to eradicate illiteracy, and the activities of cultural and educational institutions (red teahouses, red corners) are widely covered. At the same time, the entry of women into the higher education system and their work in the industrial and production sectors are also shown. The analysis in the article reveals that, along with the increase in women’s social activity, this process also served administrative and political goals.